Efficacy of ACL injury risk screening methods in identifying high-risk landing patterns during a sport-specific task - Fox, A. S.; Bonacci, J.; McLean, S. G.; Saunders, N. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Screening methods sensitive to movement strategies that increase anterior cruciate ligament (ACL) loads are likely to be effective in identifying athletes at-risk of ACL injury. Current ACL injury risk screening methods are yet to be evaluated for their ability to identify athletes' who exhibit high-risk lower limb mechanics during sport-specific maneuvers associated with ACL injury occurrences. The purpose of this study was to examine the efficacy of two ACL injury risk screening methods in identifying high-risk lower limb mechanics during a sport-specific landing task. Thirty-two female athletes were screened using the Landing Error Scoring System (LESS) and Tuck Jump Assessment. Participants' also completed a sport-specific landing task, during which three-dimensional kinematic and kinetic data were collected. One-dimensional statistical parametric mapping was used to examine the relationships between screening method scores, and the three-dimensional hip and knee joint rotation and moment data from the sport-specific landing. Higher LESS scores were associated with reduced knee flexion from 30 to 57 ms after initial contact (P = 0.003) during the sport-specific landing; however, no additional relationships were found. These findings suggest the LESS and Tuck Jump Assessment may have minimal applicability in identifying athletes' who exhibit high-risk landing postures in the sport-specific task examined.